Sex structure of the population in the city of Maribor – regarding of ageing of population - Horvat, Uroš (Journal for Geography, 2018)
The author first presents the factors that influence on the imbalance in the sex structure of the population at the global level, and then presents the situation in Slovenia and in major Slovenian cities. In the analysis is mainly used the index of femininity. It’s one of the indicators, which shows well some of the main population characteristics that result from the aging of the population, and also the decrease in fertility as well as the position of women in society. In the following, he analyzes the demographic situation in 38 local communities in the city of Maribor, and connects the process of aging of the population with differences in sex structure. He finds an increase in the share of the elderly population, which is mostly represented by retired single women who receive relatively low pensions for past work in industrial giants in Maribor. Consequently, this areas are also the areas with the highest concentration of one of the most vulnerable population groups and the areas with the highest level of risk (in most cases hidden) of poverty in Maribor.